RELATIONSHIP BETWEEN PARENTAL COMMUNICATION PATTERNS AND LANGUAGE DEVELOPMENT DELAYS IN PRE-SCHOOL CHILDREN AT THE PUTRA BANGSA AN-NUUR BOARDING SCHOOL IN KEDIRI - Eva Agustina Yalestyarini; Putri, Kanti Wahyuning Putri (Journal for Research in Public Health, 2025)
Delay in speaking is a tendency where the child is difficult in expressing desires or feelings to others such as, unable to speak clearly, and lack of vocabulary mastery that makes the child different from other children his age. This study aims to determine the Relationship between Parental Communication Patterns and Language Delay in Pre- School Age Children at Putra Bangsa An-Nuur Kindergarten, Pesantren Kediri. This study used Observational Analytic research method with Correlational Analytic design. With the Total Sampling technique, a sample of 70 respondents was obtained, the independent variable of parental communication patterns using a questionnaire and the dependent variable of language development delay. Chi-Square statistical test was used to determine the relationship between the two variables. The results of the study from 70 respondents found that most respondents had sufficient criteria in communication patterns, namely 26 respondents (74.3%) and respondents with sufficient criteria in communication patterns as many as 9 respondents (25.7%) and respondents with criteria not delayed in language development obtained 32 respondents (91.4%), and respondents with criteria delayed in language development were 3 respondents (9%). Analysis using the Chi-Square test obtained the results of p = 0.000> 0.05 which means there is a relationship between parental communication patterns and delays in language development at TK Putra Bangsa An-Nur Pesantren Kediri City. Parents who have effective communication patterns can help children develop better social and emotional skills, so that children can be better prepared to face future challenges.